The Contemporary Threats to Democracy – Legal Aspect - Wiatrowski, Piotr (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2019)
The article discusses legal aspects of threats to liberal democracy. Of particular significance among them are rulers’ disrespect for general legal principles and prioritising the will of the sovereign over those principles. Other threats include election results being distorted by election law, elected representatives overreaching their powers, reinforcing political parties and executive powers at the expense of the legislature, lobbying and excessive influence for wealthy elites, the financing of political parties by those elites and an exaggerated focus on the leader of the party. The article also discusses the demographic deficit in the European Union. That deficit takes up around 2/3 of Member States’ legislative competences and poses a threat of interference in the elective process by third countries.